Study of the features of masticatory efficiency in patients with acute cerebrovascular disorder by hemitype - K. D. Toncheva; D. M. Korol; D. D. Kindiy; M. D. Korol (Kazimierz Wielki University, 2021)
The attention of dental researchers is constantly focused on assessing the quality of treatment for various pathologies of the dentоalveolar system, determining disorders of occlusal correlations, treatment, and prevention of diseases of the temporomandibular joint and periodontal tissue pathology. Numerous studies on the above aspects contain information on the characteristics of masticatory efficiency as one of the most vivid markers of orthopedic treatment, as it allows dentists to determine the quality of actual masticatory performance. The issues of functional diagnostics at the stages of rehabilitation of patients with partial defects of the dentition remain relevant, and therefore, the indicators of masticatory efficiency in prosthetics with removable dentures will be one of the most important criteria for adaptation to them. The situation exacerbates when such patients suffer from somatic pathologies of a neurological nature, in particular, acute cerebrovascular disorder. The aim of the research was to study the features of masticatory function in patients with a complicated course of acute cerebrovascular disorder with the neurological deficit by hemitype The study involved 25 people with a complicated course of acute cerebrovascular disorder with the neurological deficit by hemitype and 20 people from the control group, aged from 40 to 65 years, for whom partial removable laminar dentures with acrylic base and retaining bent metal clasps were manufactured according to clinical indications. All patients gave their free and informed consent to participate in the study. The masticatory efficiency was determined using the author's method based on the principle of graphical analysis of fragments of the agar-agar masticatory sample with subsequent programmed calculation and computer processing of numerical data. The evaluation indicators were as follows: the total number of fragments of the chewing sample and the number of fragments with a fraction of 500-1000 pixel2. Statistical analysis of the results was conducted using the Statistica 10.0 software package for Windows, and it embraced the following: 1. Assessing the distribution of values and their correspondence to the normal one in the population. 2. Comparison of the results obtained before applying a removable dental prosthesis and 30 days after its application. 3. Intergroup comparison of the results. Thus, we observed an increase in the chewing sample parameters in the period from the beginning of orthopedic treatment until the 30th day of observation after applying a partial removable laminar denture. Despite the general trend, in the group of patients with ACVD, the masticatory efficiency was lower than that of the control group, which is confirmed by the difference between the total number of fragments (<17.22) and the number of fragments with a caliber of 500 to 1000 pixel2 (<4.41). In our opinion, this is due to the peculiarities of adaptation processes in patients with ACVD, who present with a much longer period than patients without a somatic pathology. The study revealed that the masticatory efficiency, restored by prosthetics with removable laminar dentures in the group of patients with a complicated course of ACVD by hemitype, one month after treatment is at the level of 88.68 (total number of fragments of the chewing sample) and 17.04 (number of fragments with a caliber of 500-1000 pixel2), which is a relatively worse indicator as compared to the control group. Thus, the total period of orthopedic rehabilitation for patients with ACVD is longer.